Implementasi Fuzzy Logic Untuk Identifikasi Jenis Gangguan Tegangan Secara Realtime - Ahmad Alvi Syahrin; Dimas Okky Anggriawan; Eka Prasetyono (Universitas Syiah Kuala, 2020)
In the modern era, AC voltage variations are still often a problem. This variation causes power quality decrease even damage the equipment. Voltage variations that often occur are short and long duration. The variation consist of 6 types namely Interruption, Sag, Swell, Sustained-Interruption, Undervoltage, Overvoltage. To facilitate repairs when there is a voltage variation in the electric power system, it is necessary to have an identification that can detect and distinguish any interference that occurs. Therefore, this paper proposes a fuzzy logic method for identifying types of voltage variations. This type of voltage variation identifier requires a disturbance simulator as a voltage source with varying values. To distinguish between short duration and long duration disturbances, is the time duration of the disturbance appears. The design of the voltage variation identification algorithm uses the sugeno fuzzy inference system with 2 inputs namely magnitude vrms and timer, and 1 output is the type of voltage interference. Moreover, prototype design using AMC1200 voltage sensor, microcontroller, and display. To validate the proposed algorithm, compared with standard measuring tools and simulations. Results show that the proposed algorithm has a very good performance with an accuration compared to the standard measuring instrument of 99.8%.